CONSTRUCTION OF LINEAR CODE FROM SUDOKU GRAPH - ARIYANTO , PRIHARDONO
A linear code is very important part in a telecommunication route. Tonchev (2002) showed that we can construct a code from graph with parameters meet the Gilbert-Varshamov bound. In this project, we investigate a linear code formed from sudoku graphs. In addition, we also show an analysis of the Permutation Decoding of the codes.